Facile In Situ Fabrication of Nanostructured Graphene–CuO Hybrid with Hydrogen Sulfide Removal Capacity - Lonkar, Sunil P.; Pillai, Vishnu V.; Stephen, Samuel; Abdala, Ahmed; Mittal, Vikas (Nano-Micro Letters, 2016)
A simple and scalable synthetic approach for one-step synthesis of graphene–CuO (TRGC) nanocomposite by an in situ thermo-annealing method has been developed. Using graphene oxide (GO) and copper hydroxide as a precursors reagent, the reduction of GO and the uniform deposition of in situ formed CuO nanoparticles on graphene was simultaneously achieved. The method employed no solvents, toxic-reducing agents, or organic modifiers. The resulting nanostructured hybrid exhibited improved H2S sorption capacity of 1.5 mmol H2S/g-sorbent (3 g S/100 g-sorbent). Due to its highly dispersed sub-20 nm CuO nanoparticles and large specific surface area, TRGC nanocomposite exhibits tremendous potential for energy and environment applications.